U.S. Supreme Court in the civil rights era: Deliberative Democracy and its educative institutional role, 1950s–1970s - Figueroa, Carlos (Annales. Etyka w Życiu Gospodarczym, 2019)
This article examines the U.S. Supreme Court’s lesser-known educative role as an egalitarian institution within a broader deliberative democratic process. Scholars have argued that the Court’s long asserted power of judicial review, especially in the equal protection and civil rights context, has been an over-reach of the judicial branch’s constitutional authority and responsibilities. Normative and empirical critiques have been centered on the aims of judicial review, and the challenges it poses in American political life. A core issue surrounding these critiques is that Justices are appointed not elected, and thus undermine the principle of majority rule in the U.S. constitutional democratic order. Although these critiques are legitimate in terms of claims about unelected Supreme Court Justices’ seemingly discretionary powers over elected legislative bodies, and the uncertain policy implications of judicial pronouncements on the broader society, there is, nevertheless, a positive application of judicial review as a tool Justices use as part of their educative role overcoming the so-called “counter-majoritarian difficulty.” Through a close reading of oral arguments in Brown vs. Board of Education (1954) and San Antonio vs. Rodriguez (1973)—two landmark cases invoking the Equal Protection Clause of the 14th Amendment to the federal Constitution—the article shows how appointed Justices adjudicate individual cases on appeal and attempt to educate (through an argumentative, reason-based and question-centered process) citizenlitigants and their legal representatives about the importance of equality, fairness and ethical responsibility even prior to rendering final decisions on policy controversies that have broader national social, political and economic implications.